Microwave Ablation (MWA): Basics, Technique and Results in Primary and Metastatic Liver Neoplasms – Review Article - Vogl, Thomas J.; Nour-Eldin, Nour-Eldin A.; Hammerstingl, Renate Maria; Panahi, Bita; Naguib, Nagy N. N. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2017)
Purpose The locoregional interventional oncological treatment approach is an accepted modality for liver neoplasms, especially for hepatocellular carcinoma (HCC) and oligonodular liver metastases.Materials and Methods The main aim of ablation therapies like microwave ablation (MWA) is to eradicate all malignant cells in a minimally invasive technique under imaging guidance while preserving the healthy tissue with a sufficient safety margin (at least 5 mm) surrounding the ablated lesion.Results Ablation therapy can be performed via a percutaneous, laparoscopic or intraoperative approach under ultrasound, MRI or CT guidance for adequate localization and monitoring of the ablation process.Conclusion Ablation is the method of choice for oligonodular HCCs ≤ 3 cm. The technical success rate varies from 88 % to 98 % and progression-free survival (PFS) at 3 years from 27 % to 91.7 %. The same criteria apply to the therapy of liver metastases.Key Points Citation Format
Keywords: thermal ablation; microwave ablation; hepatocellular carcinoma